THE IMPLEMENTATION OF THE MAKE A MATCH LEARNING MODEL IN AL-QUR’AN HADITH AMONG EIGHTH-GRADE STUDENTS AT HIDAYATULLAH ISLAMIC BOARDING SCHOOL, LILIRILAU DISTRICT, SOPPENG REGENCY - Raden Muliana; Muhammad Naim; Djamaluddin; St. Wardah Hanafie Das; Suredah Hamid (Journal International Inspire Education Technology, 2026)
The learning process had not been conducted effectively and optimally. The learning media used, such as whiteboards and textbooks, along with assignments in the form of monotonous worksheets, caused boredom and resulted in low learning motivation among students. Therefore, this study aimed to determine the effectiveness of the Make a Match learning model in improving students’ learning motivation in Al-Qur’an Hadith classes at Hidayatullah Islamic Boarding School. This study employed an experimental research design. The research was conducted at Hidayatullah Islamic Boarding School. The total population consisted of 259 students, and a sample of 64 students was selected and divided into three classes, including 18 students in the qualitative class. Data were collected through observations and students’ achievement scores. The data were analyzed using descriptive qualitative analysis. The findings revealed that: (1) the implementation of the Make a Match learning model in Al-Qur’an Hadith classes at Hidayatullah Islamic Boarding School demonstrated considerable potential to improve learning effectiveness and enhance both students’ and teachers’ learning experiences, although additional efforts were required to support successful and sustainable implementation; and (2) there was an increase in students’ learning motivation after the application of the Make a Match learning model in Al-Qur’an Hadith learning. This finding was supported by observation results and students’ achievement scores. The significance level obtained was 5% with a confidence level of 95% and 8 degrees of freedom. The significance value obtained was 0.000, indicating that 0.000 < ? = 0.05. Therefore, it can be concluded that the Make a Match learning model significantly improved students’ learning motivation.